PENGARUH PELATIHAN, KOMPETENSI DAN KOMITMEN TERHADAP KINERJA PETUGAS AIR TRAFFIC CONTROLLER ( ATC ) PADA PERUSAHAAN UMUM (PERUM) PENYELENGGARA PELAYANAN NAVIGASI PENERBANGAN INDONESIA ( LPPNPI ) CABANG MEDAN - Lucky Andri Rianto; Ibnu Zaiyyat Indra; Butar Marulitua Manurung; Rosdiana .; Juan Madya Edri (JRAM (Jurnal Riset Akuntansi Multiparadigma), 2020)
Air Traffic Controllers (ATC) or Air Traffic Guides are one of the keys to aviation services because they are people who serve flights from the tip of Sumatra island to the tip of Papua. Thousands of aircraft are serviced every day with arranged arrangements to avoid collisions, delays and flight schedule chaos. The great responsibility assigned to ATC makes them have specificities in education, training, competence and health standards that are different from other human resources. This study aims to determine, review and analyze training, competence, and commitment to the performance of ATC officers at PERUM LPPNPI Medan Branch. The design of this study was a descriptive analytic and quantitative survey of 71 ATC officers who worked at PERUM LPPNPI Medan as the research sample. The research data were collected by making a list of questions (questionare), interviews and documentation study. The research data will be tested using classic assumption tests (normality test, multicollinearity, heteroscedasticity) and hypothesis testing (t and f tests, determinant test).The results showed that (1) the training had a p-value (in the Sig. Column) 0.03 0.05, which means that it was significant, while the t count of 2.705 was greater than the t table of 1.995. (2) Competence has a p-value (in the Sig. Column) 0.00 0.05, which means significant, or t count 6,358 is greater than t table 1.995. (3) The commitment variable has a p-value (in the Sig. Column) of 0.01 0.05, which means significant, while the t count is 3.654 from the t table 1.995. This means that training, competence and commitment have a positive and significant effect on employee performance. Based on the research results, the following suggestions can be made: (1) Perum LPPNPI Medan Branch to further improve training evenly and continuously for the purpose of providing optimal air traffic guidance services to be realized, (2) it is necessary to promote regular discussion forums in discussing problems that occur and share the latest knowledge, (3) need to reward employees according to work performance, for example: training or educational rewards outside of their knowledge for future development, giving praise, giving certificates or souvenirs for employees, (4) leaders need fostering a trustworthy attitude towards employees can increase employee creativity and initiative, and (5) companies need to provide rewards and better monitor the performance improvement of each employee by making and publishing reports on a regular basis regarding their performance.